Teacher Activities and Adolescent Students’ Participation in a Colombian EFL Classroom (2015)
The present study concerns the activities teachers develop and ninth-graders’ participation in responses to those activities. The objectives of this study were to identify and describe the types of teaching activities developed and how students respond to them and to show how the target language is used in the classroom. The data collection was conducted through daily field notes and a diary. The findings show that in the classroom, the teacher develops twelve types of activities, and the percentage of use of the target language is low.El presente estudio da cuenta del tipo de actividades desarrolladas por una maestra y la respuesta/participación de los estudiantes del grado noveno en esas actividades. Los objetivos de esta investigación fueron identificar y describir el tipo de actividades desarrolladas, la forma como los estudiantes responden a éstas y mostrar el uso de la lengua extranjera en el salón de clase. Para recolectar los datos se usó registro diario de y un diario de campo. Los resultados muestran que en el salón de clases la docente desarrolla doce tipos de actividades y que el porcentaje de uso de lengua extranjera es bajo.